THE STUDY OF CYANIDIN PROTOLYTIC PROPERTIES BY CHEMICAL CHROMATICY METHOD - A. N. Chebotaryov; D. V. Snigur; H. M. Guzenko; I. S. Efimova; T. M. Shcherbakova (Vìsnik Odesʹkogo Nacìonalʹnogo Unìversitetu: Hìmìâ, 2014)
The calculations of chromaticity yellowness index function and the CIE color difference function were made for cyanidin aqueous solutions based on the array of spectrophotometry data in a wide range of medium’s acidity (рН). It was shown the principal possibility to use the yellowness index and CIE color difference chromaticity functions for ionization constants determination of cyanidin.